Young man with acute pain in the hypogastrium: What is the diagnostic?. Issue 9 (22nd July 2018) - Jabbour, Youness; Regragui, Souhail
Key Clinical Message: Congenital renal anomalies can stay asymptomatic even until adult age and be revealed by occurrence of complications. Clinicians should keep in mind this eventuality, especially in the countries where screening for congenital abnormalities is not adopted. Ultrasound in front of abdominal pain is useful and can sometimes rectify the diagnosis. Abstract : Congenital renal anomalies can stay asymptomatic even until adult age and be revealed by occurrence of complications. Clinicians should keep in mind this eventuality, especially in the countries where screening for congenital abnormalities is not adopted. Ultrasound in front of abdominal pain is useful and can sometimes rectify the diagnosis.